Oxidative stress reduction related to the efficacy of n-3 polyunsaturated fatty acids in first episode schizophrenia: Secondary outcome analysis of the OFFER randomized trial. (June 2017) - Pawełczyk, T.; Grancow-Grabka, M.; Trafalska, E.; Szemraj, J.; Pawełczyk, A.
Abstract: Intervention studies of n-3 polyunsaturated fatty acids (n-3 PUFA) as add-on therapy in patients with schizophrenia have not examined changes in oxidative stress. A randomized placebo-controlled trial of a 26-week intervention composed of 2.2 g/day of n-3 PUFA was found to reduce symptom severity in first-episode schizophrenia patients. The present study is an extension of our previous report, whose secondary aim was to assess the association between the clinical effect of n-3 PUFA and changes in oxidative stress indices. Seventy-one patients aged 16–35 were enrolled in the study and randomly assigned to the study arms. Total plasma antioxidant capacity and 8-epi-isoprostane F2α content were assessed at baseline and at weeks 8 and 26 of the study as secondary outcome measures. Significant changes in oxidative stress indices favouring the intervention group were observed: decreases in 8-isoprostane F2α (p<0.001) and increases in total plasma antioxidant capacity (p<0.001). Significant correlations between changes in clinical scores relevant to symptom severity and changes in oxidative indices were observed. The results of the present study hence suggest that the efficacy of a six-month intervention with n-3 PUFA observed in first-episode schizophrenia may be related to improvement in oxidative stress indices. Highlights: N-3 PUFA efficacy is related to oxidative stress indices in schizophrenia. N-3 PUFA and placebo group presented with significant decrease in 8-epi-iso-PGF2α . Both groups showed increase in total plasma anti-oxidant capacity (TAC). The changes in 8-epi-iso-PGF2α and TAC were significantly higher in n-3 PUFA group. Clinical improvement and oxidative indices change were significantly correlated.